The comparative analysis of the indoor air pollutants in occupied apartments at residential area and industrial area in dubai, united arab emirates - Jung, Chuloh; Alqassimi, Nahla; El Samanoudy, Gamal (Frontiers in Built Environment, 2022)
Most of the research on indoor air pollutants in the United Arab Emirates (UAE) focus on the state before moving in. There are no studies on the evaluation and characteristics of Indoor Air Quality (IAQ) in living conditions. This study aims to obtain primary data by measuring the concentration of indoor hazardous chemical substances in apartment housings with different area characteristics and to identify the external and internal pollutants that affect them. As a methodology, a comparative analysis was conducted between residential (Business Bay) and industrial areas (Ras Al Khor) to investigate the indoor air pollutants level with the comparison of the outdoor environment, elapsed time after construction, finished materials, temperature, relative humidity, renovation, purchase of furniture and electric appliances, built-in closets, and air cleaning methods. The result showed that Benzene (C6H6), Toluene (C7H8), Ethylbenzene (C8H10), Xylene (C8H10), and Styrene (C8H8) were at a stable level. However, in the case of Formaldehyde (HCHO), points exceeding or close to the WHO IAQ standard were found, suggesting that long-term attention is required. The differences between residential and industrial areas were marginal in terms of the size of the house, temperature and humidity, and the building materials. It was proven that the emission of indoor air pollutants from building materials lessened under 18 months after construction.